Accuracy of Energy Expenditure Estimation by Activity Monitors Differs with Ethnicity - Brazeau, A.-S.; Suppere, C.; Strychar, I.; Belisle, V.; Demers, S.-P.; Rabasa-Lhoret, R. (International Journal of Sports Medicine, 2014)
The aim of this project is to explore the accuracy of 2 activity monitors (SenseWear Armband & Actical) to estimate energy expenditure during rest and light to moderate intensity exercises in 2 ethnic groups. 18 Caucasian and 20 Black adults (age: 26.8±5.2 years; body mass index: 23.9±3.0 kg/m2) wore the 2 devices simultaneously during 3 standardised activities: 30-min rest, 45-min of treadmill at 40% of their V˙O2peak and 45-min of stationary cycling at 50% of their V˙O2peak. Energy estimated with the 2 devices was compared to indirect calorimetry measurements. Both devices overestimated energy expenditure during rest (SenseWear: 36% in Black vs. 16% in Caucasian; Actical: 26% vs. 11%, p<0.01 between groups) and treadmill (SenseWear: 50% vs. 25%; Actical: 67% vs. 32%, p<0.01 between groups). Both devices significantly underestimated energy expenditure during stationary cycling (SenseWear: 24% vs. 26%; Actical: 58% vs. 70%, p=NS between groups). Equations used to estimate energy expenditure from accelerometer data is less precise among Black adults than Caucasian adults. Ethnic-specific formulas are probably required.
Keywords: physical activity energy expenditure; resting energy expenditure; activity monitoring; accelerometry